Feasibility and Efficacy of a Parent-Focused, Text Message-Delivered Intervention to Reduce Sedentary Behavior in 2- to 4-Year-Old Children (Mini Movers): Pilot Randomized Controlled Trial - Downing, Katherine L; Salmon, Jo; Hinkley, Trina; Hnatiuk, Jill A; Hesketh, Kylie D (JMIR Publications, 2018)
BackgroundDespite public health guidelines to limit sedentary behavior, many young children spend large amounts of time sedentary (eg, screen and sitting time) during waking hours. ObjectiveThe objective of this study was to test the feasibility and efficacy of a parent-focused, predominantly text message-delivered intervention to support parents to reduce the amount of time their children spend in sedentary behavior. MethodsMini Movers was a pilot randomized controlled trial delivered to parents of 2- to 4-year-old children in Melbourne, Australia. Participants were recruited through playgroups, social media, and snowball sampling. Eligibility criteria were having an ambulatory child (2-4 years), English literacy, and smartphone ownership. Participants were randomized to intervention or wait-list control on a 1:1 ratio after baseline data collection. The 6-week intervention was predominantly delivered via text messages, using a Web-based bulk text message platform managed by the interventionist. Intervention strategies focused on increasing parental knowledge, building self-efficacy, setting goals, and providing reinforcement, and were underpinned by the Coventry, Aberdeen & London-Refined taxonomy of behavior change techniques and social cognitive theory. The primary outcome was intervention feasibility, measured by recruitment, retention, intervention delivery, and fidelity; process evaluation questionnaires; and qualitative interviews with a subsample of participants. Secondary outcomes were children's screen and restraint time (parent report), sitting time (parent report, activPAL), and potential mediators (parent report). Linear regression models were used to determine intervention effects on secondary outcomes, controlling for the child's sex and age and clustering by playgroup; effect sizes (Cohen's d) were calculated. ResultsA total of 57 participants (30 intervention; 27 wait-list control) were recruited, and retention was high (93%). Process evaluation results showed that the intervention was highly acceptable to parents. The majority of intervention components were reported to be useful and relevant. Compared with children in the control group, children in the intervention group had significantly less screen time postintervention (adjusted difference [95% CI]=−35.0 [−64.1 to −5.9] min/day; Cohen's d=0.82). All other measures of sedentary behavior were in the expected direction, with small to moderate effect sizes. ConclusionsMini Movers was shown to be a feasible, acceptable, and efficacious pilot intervention for parents of young children, warranting a larger-scale randomized control trial. Trial RegistrationAustralian New Zealand Clinical Trials registry: ACTRN12616000628448; https://www.anzctr.org.au/ Trial/Registration/TrialReview.aspx?ACTRN=12616000628448p (Archived by WebCite at http://www.webcitation.org/ 6wZcA3cYM)